Quality of match for statistical matches using the American Time Use Survey 2010, the Survey of Consumer Finances 2010, and the annual social and economic supplement 2011 - Fernando Rios-Avila (Levy Economics Institute of Bard College, 2014)
This paper describes the quality of the statistical matching between the March 2011 supplement to the Current Population Survey and the 2010 American Time Use Survey and Survey of Consumer Finances, which are used as the basis for the 2010 LIMEW estimates for the United States. In the first part of the paper, the alignment of the datasets is examined. In the second, various aspects of the match quality are described. The results indicate that the matches are of high quality, with some indication of bias in specific cases.
Keywords: C14; C40; D31; 330; Statistical Matching; American Time Use Survey; Survey of Consumer Finances; LIMEW; United States